UPAYA MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS IPS SISWA MELALUI PEMBELAJARAN DISCOVERY LEARNING DI SDN 111 PEKANBARU - Elpri Darta Putra; Siti Quratul Ain; Eva Astuti Mulyani; Mitha Dwi Anggriani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the teacher's efforts in improving students’ social studies critical thinking skills through the discovery model at SDN 111 Pekanbaru. The research design used was CAR (Classroom Action Research). This research was conducted on fifth-grade students of SD Negeri 111 Pekanbaru in the odd semester of the 2020/2021 Academic Year, with 27 students. This classroom action research was conducted through four stages: planning, implementation, observation, and reflection. This research consisted of 2 cycles. Each cycle consisted of planning, implementation, observation, and reflection to continue the next cycle.Meanwhile, the data analysis technique in this study was descriptive statistical analysis to describe data about the teachers’ and students’ activities to be observed. The results were that the Discovery Learning model improved students' critical thinking, which was seen from students’ learning outcomes in social studies subjects at grade V of SDN 111 Pekanbaru. Obviously, the social studies learning process before the implementation of the Discovery Learning model had a low percentage level, namely 3.70%. Meanwhile, after implementing the Discovery Learning model, there was a significant increase. In the first cycle, the results were 37.04%, while in the second cycle, the learning outcomes were 92.59%, with the number of students who completed as many as 25 students from 27 students at grade V of SDN 111 Pekanbaru.